Creative Competencies and Cognitive Processes Associated with Creativity are Linked with Positive Schizotypy. Issue 2 (2nd April 2020) - Jacquet, Jennifer; Delpech, Lionel; Bronchain, Jonathan; Raynal, Patrick
ABSTRACT: The links between schizotypy and creativity remain ill-defined. This study assessed creative competencies and cognitive processes associated with creativity in groups of individuals with distinct levels of schizotypy dimensions. Groups were obtained through cluster analysis of a large student sample ( N = 946). All dimensions of creative competencies (Capturing, Broadening, Surrounding, Challenging) were higher in a pure positive schizotypy cluster than in clusters characterized by negative schizotypy or low schizotypy. Regarding creative processes associated with creativity, two dimensions, namely Imagery and Incubation, were higher in the pure positive schizotypy cluster than in negative schizotypy or low schizotypy clusters, while other dimensions (Brainstorming, Idea manipulation, Imagery, Incubation) were higher in positive schizotypy cluster when compared with negative schizotypy groups. This supports the notion that creative cognitive processes are more developed in positive than in negative schizotypy. Most interestingly, it also suggests that positive schizotypy can be beneficial even when compared with non-schizotypal individuals, since all dimensions of creative competencies and two dimensions of creative cognitive processes were higher in individuals with high positive schizotypy than in those with low schizotypy. This could have implications to improve the difficult and stigmatizing personal experience of individuals with high positive schizotypy about their own symptoms.